Microbiota-derived short-chain fatty acids: Implications for cardiovascular and metabolic disease - Lu, Yingdong; Zhang, Yang; Zhao, Xin; Shang, Chang; Xiang, Mi; Li, Li; Cui, Xiangning (Frontiers in Cardiovascular Medicine, 2022)
Cardiovascular diseases (CVDs) have been on the rise around the globe in the past few decades despite the existing guidelines for prevention and treatment. Short-chain fatty acids (SCFAs) are the main metabolites of certain colonic anaerobic bacterial fermentation in the gastrointestinal tract and have been found to be the key metabolites in the host of CVDs. Accumulating evidence suggest that the end-products of SCFAs (including acetate, propionate, and butyrate) interact with CVDs through maintaining intestinal integrity, anti-inflammation, modulating glucolipid metabolism, blood pressure, and activating gut-brain axis. Recent advances suggest a promising way to prevent and treat CVDs by controlling SCFAs. Hence, this review tends to summarize the functional roles carried out by SCFAs that are reported in CVDs studies. This review also highlights several novel therapeutic interventions for SCFAs to prevent and treat CVDs.